Passive transfer studies in demyelinating neuropathy with IgM monoclonal antibodies to myelin-associated glycoprotein. Issue 9 (September 1985) - Steck, A J; Murray, N; Justafre, J C; Meier, C; Toyka, K V; Heininger, K; Stoll, G
Abstract : Serum or IgM fraction from two patients with a demyelinating neuropathy and IgM monoclonal antibodies to myelin-associated glycoprotein were injected in three different animal species. There were no clinical, electrophysiological or morphological signs of demyelination in either chronic or acute passive transfer experiments. These results suggest that the pathogenesis of this human demyelinating neuropathy may be more complex than has been assumed.